FARMER CHEESE IN NUTRITION OF TENDER AGE CHILDREN: TRADITIONS AND MODERN OPPORTUNITIES - E. А. Samorodnova (Вопросы современной педиатрии, 2014)
Farmer cheese is a food source of the milk protein, easily acquired milk fat, vitamins, folic and nicotinic acid, macro- and microelements, methionine — irreplaceable amino acid with lipotropic action. Recommendations on farmer cheese inclusion to a food ration of a tender age child are provided. The data on the range and advantages of the children farmer cheese made by ultrafiltration method allowing to receive a product with the optimum organoleptic properties, enriched with serumal proteins with necessary amount of calcium and phosphorus, with high degree of microbiological purity are submitted.